Keragaman Jamur Antagonis Pada Rhizosfer Karet (Hevea Brassiliensis Muell.Arg.) Sehat dan Terserang Jamur Akar Putih (Rigidoporus Microporus (Swartz: Fr) - irma aryani; Lisnawita Lisnawita; Lahmuddin Lubis (Jurnal Agroekoteknologi, 2019)
The beneficial microorganisms in the rhizosphere are very abundant. This potential, especially antagonistic fungi can be used to control soil-borne pathogens, including in controlling white root rot disease which is a soil-borne pathogen. This study aims to determine the antagonistic fungal diversity of healthy rubber rhizosphare and infected with white root rot disease. This research was conducted in Plant Disease Laboratory, Faculty of Agriculture, Universitas Sumatera Utara from October 2017 until March 2018. The research was conducted by collecting of soil samples from healthy rubber plant and infected white root rot disease in rubber plantation of Silomlom Village, Simpang Empat Sub-district, of Asahan Regency then soil samples were isolated in the Laboratory until obtained a pure fungi isolates and antagonistic test and identified to the genus level. The results showed that fungi obtained in healthy plant rhizosphere were Mortierella, Humicola, Fusarium, Aspergillus, Gliocladium, Penicillium, Trichoderma and on the plant rhizosphare attacted white root disease obtained fungi Trichoderma, Humicola, and Phialophora. The results of antagonistic test showed that the highest inhibition was Mortierella that was 90%, then Trichoderma was 71.85%, Aspergillus 66.46% and the lowest was Humicola 27.78%.